Marijuana Enforcement in Nebraska (2009-2014) - Spohn, Ryan E. (2016)
With the passage of Amendment 64 in 2012, the people of Colorado legalized the sale of recreational marijuana. While early evidence suggests that the policy change was both a cost cutting measure for Colorado law enforcement as well as a significant source of state revenue (an estimated $80 million), such benefits have not been shared among states that border Colorado. In fact, marijuana remains prohibited in states such as Nebraska, where criminal justice officials have reported that marijuana arrests and jail admissions have increased significantly in the past half-decade, particularly in counties on the Colorado border, in the panhandle, and along Interstate 80. Officials also claimed that the most significant increases occurred during 2014, which was the first year recreational marijuana dispensaries opened their doors to both in and out of state residents